A survey on privacy impacts of digital investigation - Daryabar, Farid; Dehghantanha, Ali; Udzir, Nur Izura; Mohd Sani, Nor Fazlida; Shamsuddin, Solahuddin; Norouzizadeh, Farhood (Advanced Institute of Convergence Information Technology, 2013)
Digital forensics is becoming more and more demanding as computers evolve into different platforms and penetrate different industries. The usage of computers in today’s society has covered in vast areas and are implemented in fields where the most sensitive information are stored and accessed for various operations. This paper will look into developmental trends of applications of digital forensics and security in various aspects within the span of 7 years based on critical review and statistical analysis, and then contribute the results of significant change and shift of focus in digital forensics development. Then, a discussion will be made on privacy concerns, whether the current development trend is paying more attention to privacy preservation or harsh forensic investigation techniques that usually result in compromised personal information.